Risk factors for antimicrobial resistance in patients with Escherichia coli bacteraemia related to urinary tract infection. Issue 4 (December 2022) - Balfour, James; Barclay, Mabel; Danial, Janathan; Philip, Carol; Perry, Meghan; Etherson, Michelle; Henderson, Naomi
Summary: Introduction: NHS Lothian policy has recently changed to avoid first-line use of trimethoprim for uncomplicated urinary tract infections (UTI) in patients with risk factors for trimethoprim resistance, in line with national guidance. This study aimed to identify risk factors for antimicrobial resistance in Escherichia coli bacteraemia related to UTI. Methods: A retrospective cohort study of 687 patients with E. coli bacteraemia related to UTI in NHS Lothian from 01/02/18 to 29/02/20 was undertaken. Demographics and comorbidities were collected from electronic patient records. Community prescribing and microbiology data were collected from the prescribing information system and Apex. Univariate and multivariate analysis was undertaken using RStudio to analyse trimethoprim, gentamicin and multi-drug resistance (MDR). Results: Trimethoprim resistance was present in 282/687(41%) of blood culture isolates. MDR was present in 278/687(40.5%) isolates. Previous urinary trimethoprim resistant E. coli was a significant risk factor for both trimethoprim resistance (OR 9.44, 95%CI 5.83–15.9) and MDR (OR 4.81, 95%CI 3.17–7.43) on multivariate modelling. Trimethoprim prescription (OR 2.10, 95% CI 1.33–3.34) and the number of community antibiotic courses (OR 1.19, 95%CI 1.06–1.35) were additional risk factors for trimethoprim resistance. Multiple independent risk factors were also identified for trimethoprim resistance, MDR and gentamicin resistance. Discussion: This study showed a high prevalence of trimethoprim resistance and MDR in patients with E. coli bacteraemia related to UTI. This supports the withdrawal of trimethoprim from first-line treatment of UTIs in patients with risk factors for trimethoprim resistance. It has also identified risk factors for MDR in E. coli bacteraemia.